ASC annual report 2017-18 (Annual report Australian Sports Commission, 2018)
This report has been prepared in accordance with parliamentary reporting and legislative requirements and provides details of the ASC`s performance and operations for the financial year ending 30 June 2018. The report details how effective the ASC has been at achieving its outcomes for the year as outlined in the ASC 2017-21 Corporate Plan and the 2017-18 Portfolio Budget Statements.